Dietary nitrate reduces muscle metabolic perturbation and improves exercise tolerance in hypoxia - Vanhatalo, Anni; Fulford, Jonathan; Bailey, Stephen J.; Blackwell, James R.; Winyard, Paul G.; Jones, Andrew M. (The Journal of physiology, 2011)
Non‐Technical Summary  Reduced atmospheric O2 availability (hypoxia) impairs muscle oxidative energy production and exercise tolerance. We show that dietary supplementation with inorganic nitrate reduces markers of muscle fatigue and improves high‐intensity exercise tolerance in healthy adults inhaling air containing 14.5% O2. In the body, nitrate can be converted to nitrite and nitric oxide. These molecules can improve muscle efficiency and also dilate blood vessels allowing more O2 to be delivered to active muscle. These results suggest that dietary nitrate could be beneficial during exercise at moderate to high altitude and in conditions where O2 delivery to muscle is reduced such as in pulmonary, cardiovascular and sleep disorders. Exercise in hypoxia is associated with reduced muscle oxidative function and impaired exercise tolerance. We hypothesised that dietary nitrate supplementation (which increases plasma [nitrite] and thus NO bioavailability) would ameliorate the adverse effects of hypoxia on muscle metabolism and oxidative function. In a double‐blind, randomised crossover study, nine healthy subjects completed knee‐extension exercise to the limit of tolerance (Tlim), once in normoxia (20.9% O2; CON) and twice in hypoxia (14.5% O2). During 24 h prior to the hypoxia trials, subjects consumed 0.75 L of nitrate‐rich beetroot juice (9.3 mmol nitrate; H‐BR) or 0.75 L of nitrate‐depleted beetroot juice as a placebo (0.006 mmol nitrate; H‐PL). Muscle metabolism was assessed using calibrated 31P‐MRS. Plasma [nitrite] was elevated (P < 0.01) following BR (194 ± 51 nm) compared to PL (129 ± 23 nm) and CON (142 ± 37 nM). Tlim was reduced in H‐PL compared to CON (393 ± 169 vs. 471 ± 200 s; P < 0.05) but was not different between CON and H‐BR (477 ± 200 s). The muscle [PCr], [Pi] and pH changed at a faster rate in H‐PL compared to CON and H‐BR. The [PCr] recovery time constant was greater (P < 0.01) in H‐PL (29 ± 5 s) compared to CON (23 ± 5 s) and H‐BR (24 ± 5 s). Nitrate supplementation reduced muscle metabolic perturbation during exercise in hypoxia and restored exercise tolerance and oxidative function to values observed in normoxia. The results suggest that augmenting the nitrate–nitrite–NO pathway may have important therapeutic applications for improving muscle energetics and functional capacity in hypoxia.